Anharmonic effective potential, thermodynamic parameters, and EXAFS of hep crystals - Hung, Nguyen Van; Hai, Ngo Trong; Tien, Tong Sy; Hung, Le Hai (VNU Journal of Science: Mathematics - Physics, 2009)
Abstract